Imbalance of the Humoral Component of the Immune System as a Basis for the Progression of Non-Alcoholic Fatty Liver Disease in Patients with Obesity and Concomitant Biliary Tract Pathology - Filippova, Aleksandra (Archive of Clinical Medicine, 2016)
The objective of the research was to study the features of the indicators of the humoral component of the immune system depending on the body mass index in patients with non-alcoholic hepatic steatosis, non-alcoholic steatohepatitis, concomitant obesity and biliary tract pathology.Material and methods. 200 patients with non-alcoholic fatty liver disease, concomitant obesity and biliary tract pathology including 100 patients with non-alcoholic hepatic steatosis and 100 with non-alcoholic steatohepatitis were examined. 70 out of 100 patients with non-alcoholic steatohepatitis had the minimum level of alanine transaminase activity and 30 patients had a moderate alanine transaminase activity. The control group included 30 apparently healthy persons. The body mass index was determined using the Quetelet formula. All the patients with non-alcoholic hepatic steatosis and non-alcoholic steatohepatitis were divided into three groups depending on the increase in the body mass index and the presence of biliary tract pathology. The humoral immune system state was evaluated by the levels of immunoglobulins A, M and G and the content of circulating immune complexes. Results. In patients with non-alcoholic hepatic steatosis and non-alcoholic steatohepatitis, concomitant obesity and biliary tract pathology, there were observed abnormalities in the humoral component of the immune system with possible increase in the levels of major immunoglobulin classes as well as in the content of circulating immune complexes being more pronounced in patients with non-alcoholic steatohepatitis compared to patients with non-alcoholic hepatic steatosis (p<0.05) and apparently healthy persons (p<0.001). The increase in the body mass index led to a significant increase in the levels of Ig A, M, G and the activation of circulating immune complexes.More significant changes in humoral indices were observed in patients with chronic non-calculous and calculous cholecystitis in the presence of inflammatory biliary tract changes during the exacerbation of the pathology compared to patients who underwent cholecystectomy on the background of the aggravation of postcholecystectomy syndrome.Conclusions. The obtained data indicated that one of the elements in the pathogenesis of non-alcoholic fatty liver disease with concomitant obesity and biliary tract pathology is a significant change in the indicators of humoral immunity, namely the increase in the levels of Ig (A, M, G) and circulating immune complexes which depend on the clinical form (non-alcoholic hepatic steatosis or non-alcoholic steatohepatitis), increase in the body mass index and the presence of biliary tract comorbidity.